1998
DOI: 10.1055/s-2007-1010212
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Thoracic Sonography

Abstract: In contrast to its use in other surgical disciplines, intraoperative sonography has so far been of minor importance in thoracic surgery. The technique of intrathoracic, intraoperative, ultrasonic examination was applied in 85 patients with different indications: in 61 patients during thoracoscopy, in 24 patients during open thoracic surgery. 6 patients eventually underwent a combination of both procedures. In order to improve the intrathoracic maneuverability of the sonographic probe we developed an electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…As an alternative to hook-wire placement, CT-guided percutaneous staining with methylene blue can be used. Intraoperative sonography is one of the last localization techniques to be introduced, but it soon showed several intraoperative advantages such as its repeatability, the lack of complications and/or morbidity related to the method, its ability to define margins, dimensions and structural characteristics of the lesions and their own adjacent structures and its low cost [4,5,7,10]. Furthermore, it does not cause exposure to ionizing radiation, it can be used for multiple and bilateral lesions and it is able to localize lesions less than 10 mm in diameter which might not be visualized at preoperative exams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to hook-wire placement, CT-guided percutaneous staining with methylene blue can be used. Intraoperative sonography is one of the last localization techniques to be introduced, but it soon showed several intraoperative advantages such as its repeatability, the lack of complications and/or morbidity related to the method, its ability to define margins, dimensions and structural characteristics of the lesions and their own adjacent structures and its low cost [4,5,7,10]. Furthermore, it does not cause exposure to ionizing radiation, it can be used for multiple and bilateral lesions and it is able to localize lesions less than 10 mm in diameter which might not be visualized at preoperative exams.…”
Section: Discussionmentioning
confidence: 99%
“…Friedel et al report 90% of visualized lesions in 42 patients with peripheral coin lesions; 16% of these were not detectable by thoracoscopy or by palpation with grasping forceps [10].…”
Section: Introductionmentioning
confidence: 99%
“…Extrathoracic ultrasonography can be used successfully in the diagnosis of pleural conditions. It was used under local anesthesia and also in children with VATS [1,[6][7][8][9][10][11][12][13][14]. Ultrasonography was applied to 85 patients with different indications.…”
Section: Discussionmentioning
confidence: 99%
“…Developed an intrathoracic ultrasonic probe and used it in 61 patients during thoracoscopy and 24 patients during open thoracic surgery. Their study showed that thoracoscopic had high sensitivity for localization of intrapulmonary tumors [1]. Wada and colleagues convex probe ultrasound was used in their study was to assess thoracoscopic localization and biopsy of subcentimetre pulmonary nodules in porcine and rabbit lung models [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation